Distorted body image influences body schema in individuals with negative bodily attitudes. (January 2019) - Irvine, Kamila R.; McCarty, Kristofor; McKenzie, Kirsten J.; Pollet, Thomas V.; Cornelissen, Katri K.; Tovée, Martin J.; Cornelissen, Piers L.
Abstract: There is now a considerable body of evidence to suggest that internal representations of the body can be meaningfully separated into at least two general levels; body image as a perceptual construct and body schema as a motor metric. However, recent studies with eating disordered individuals have suggested that there may in fact be more interaction between these two representations than first thought. We aimed to investigate how body image might act to influence body schema within a typical, healthy population. 100 healthy adult women were asked to judge the smallest gap between a pair of sliding doors that they could just pass through. We then determined whether these estimates were sufficient to predict the size of the smallest gap that they could actually pass through, or whether perceptual and attitudinal body image information was required in order to make these predictions. It was found that perceptual body image did indeed mediate performance on the egocentric (but not allocentric) motor imagery affordance task, but only for those individuals with raised body image concerns and low self-esteem; body schema was influenced by both the perceptual and attitudinal components of body image in those with more negative bodily attitudes. Furthermore, disparities between perceived versus actual size were associated with body parts that had larger variations in adipose/muscle-dependent circumference. We therefore suggest that it may be the affective salience of a distorted body representation that mediates the degree to which it is incorporated into the current body state. Highlights: BMI and attitudinal body image were predictive of participants' perceptual body image judgements. Affordance judgments were only influenced by body areas with large variation in adiposity/muscle. In women with bodily concerns affordance judgements incorporate distorted perceptual body image. Body schema was influenced by both the perceptual and attitudinal components of body image.